Corneal trophic ulcer one week after topical diclofenac use - Lasota, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
A 65-year-old woman operated on for cataract was discharged from hospital with a routine prescription including diclofenac. One week later she was diagnosed with corneal trophic ulcer in the operated eye. As the non-operated eye suffered from filamentary keratopathy, the hypothesis of a serious adverse event due to diclofenac was considered. Diclofenac was stopped and intensive topical non-preservative tears were administered. No further melting was noticed and epithelialization of the cornea occurred. Diclofenac as a non-steroidal anti-inflammatory drug is known for its anesthetic action on the cornea. This effect contributes to aggravation of the pre-existing dry eye syndrome related to Sjögren syndrome (diagnosed a posteriori) with potential for corneal perforation. Therefore the prescription of diclofenac should be preceded by questioning the patient about the predisposing rheumatoid conditions and careful examination of the eye.